Striking Dependence of Protein Sweetness on Water Quality: The Role of the Ionic Strength - Delfi, Masoud; Emendato, Alessandro; Temussi, Piero Andrea; Picone, Delia (Frontiers in Molecular Biosciences, 2021)
Sweet proteins are the sweetest natural molecules. This aspect prompted several proposals for their use as food additives, mainly because the amounts to be added to food would be very small and safe for people suffering from sucrose-linked diseases. During studies of sweet proteins as food additives we found that their sweetness is affected by water salinity, while there is no influence on protein’s structure. Parallel tasting of small size sweeteners revealed no influence of the water quality. This result is explained by the interference of ionic strength with the mechanism of action of sweet proteins and provides an experimental validation of the wedge model for the interaction of proteins with the sweet receptor.